(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The paper aims at determining the impact of Covid-19 related psychological distress on the E-mobile banking adoption in the emerging countries’ post Covid-19 era with the extended TAM model and the case of Vietnam. The primary data with a total of 483 Vietnamese people who are above 16 years old participated in this study, and the stuctural equation modeling was employed to verify the conceptual framework. The results showed that TAM extended constructs, namely Perceived Usefulness, Perceived Ease of Use and Trust influence the Attitude towards E-mobile banking. The intention to use was significantly predicted by the Covid-19 related psychological distress and the Attitude towards E-mobile banking. Based on these findings, recommendations were proposed to enhance the e-mobile banking adoption by enhancing the usefulness and trust of customers on using e-mobile banking services.